1999
DOI: 10.1002/(sici)1521-3765(19990702)5:7<2069::aid-chem2069>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Biphasic Catalyzed Telomerization of Butadiene and Ammonia: Kinetics and New Ligands for Regioselective Reactions

Abstract: The kinetics of the palladiumcatalyzed biphasic telomerization of butadiene and ammonia by means of in situ catalysts consisting of phosphane palladium complexes were investigated at 80 8C. The effects of ligand, catalyst, and ammonia concentrations were studied. The rate of product formation as well as the regioselectivity of the reaction was found to depend greatly on ligand and catalyst concentration. A model for the reaction mechanism was deduced from these results, explaining the regioselectivities obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 11 publications
1
36
0
1
Order By: Relevance
“…Several functional groups such as chloro, bromo, and methoxycarbonyl, can be tolerated in these reactions (Table 1, entries [4][5][6][7][8]. It has been also found that higher yields are obtained by using a larger amount (30 mol%) of base (NaHCO 3 ) in large-scale reactions of ammonium acetate with benzylic alcohols, although we have already reported that 6 mol% of sodium bicarbonate is used in smaller scale reactions.…”
Section: Scope and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several functional groups such as chloro, bromo, and methoxycarbonyl, can be tolerated in these reactions (Table 1, entries [4][5][6][7][8]. It has been also found that higher yields are obtained by using a larger amount (30 mol%) of base (NaHCO 3 ) in large-scale reactions of ammonium acetate with benzylic alcohols, although we have already reported that 6 mol% of sodium bicarbonate is used in smaller scale reactions.…”
Section: Scope and Limitationsmentioning
confidence: 99%
“…3 Ammonia or simple salts are attractive nitrogen sources for the synthesis of amines and there have been some reports on homogeneous catalytic systems using it as the substrate. [4][5][6][7] Thus, the utilization of ammonia or its simple salts as nitrogen sources has been an important objective in catalytic organic chemistry. The reported catalytic systems so far have described the synthesis of primary alkyl-and arylamines, as well as secondary and tertiary arylamines, while, to the best of our knowledge, there has been no report on the selective catalytic synthesis of di-and trialkylamines from ammonia or its simple salts.…”
Section: Introductionmentioning
confidence: 99%
“…It is supposed that the main reason for the predominant formation of the linear product is the formation of a trigonal planar (1,6-diene) palladium D complex which is more stable compared to the (1,7-diene) palladium complex C (Scheme 3). Considering the TXTPS ligand, due to the presence of methyl group, its p-acceptor behaviour decreases while the steric hindrance increases [37]. This favours the attack at the C 1 center which is less electron-rich in that case.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the abundance and low price of ammonia, much attention has been focused on its use as a nitrogen source for organic synthesis [4,5]. Recent reports on homogenous catalytic systems using ammonia as the substrate include palladium-catalyzed telomerization of butadiene and ammonia giving primary alkylamines [6], Pd-catalyzed allylic amination [7], copper-and palladiumcatalyzed coupling reactions of ammonia with aryl halides to form arylamines [8][9][10], rhodium-and iridium-catalyzed reductive aminations of carbonyl compounds with ammonium formate and ammonia to afford primary alkylamines [11][12][13] and palladium-catalyzed arylation of ammonia to afford di-and triarylamines [10].…”
Section: Introductionmentioning
confidence: 99%